2019
DOI: 10.1136/bmjopen-2019-029425
|View full text |Cite
|
Sign up to set email alerts
|

The NoHoW protocol: a multicentre 2×2 factorial randomised controlled trial investigating an evidence-based digital toolkit for weight loss maintenance in European adults

Abstract: IntroductionObesity and associated diseases place a severe burden on healthcare systems. Behavioural interventions for weight loss (WL) are successful in the short term but often result in weight regain over time. Self-regulation of eating and activity behaviours may significantly enhance weight loss maintenance (WLM) and may be effectively augmented by contextual behavioural approaches to emotion regulation. The NoHoW trial tests the efficacy of a theoretically informed, evidence-based digital toolkit using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 89 publications
(92 reference statements)
0
59
0
Order By: Relevance
“…It was delivered in three centres located in the United Kingdom (Leeds), Denmark (Copenhagen), and Portugal (Lisbon). A detailed description of the trial can be found elsewhere [33]. In short, eligible participants were randomised into 4 arms upon entry to the trial ((1) active control, (2) self-regulation and motivation, (3) contextual behavioural emotion regulation and (4) self-regulation, motivation and emotion regulation (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was delivered in three centres located in the United Kingdom (Leeds), Denmark (Copenhagen), and Portugal (Lisbon). A detailed description of the trial can be found elsewhere [33]. In short, eligible participants were randomised into 4 arms upon entry to the trial ((1) active control, (2) self-regulation and motivation, (3) contextual behavioural emotion regulation and (4) self-regulation, motivation and emotion regulation (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to weigh themselves at least twice per week and wear the activity monitor at all times apart from when charging and during activities involving water. No specific dietary or physical activity advice was given, though intervention content (which is provided in more detail elsewhere [33]) provided guidance on self-regulation and planning which may support a healthy lifestyle. Outcome measures were made at 6, 12 and 18 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of the baseline examination in the Danish part of the NoHoW study [29], which is a multi-centre randomised controlled trial focusing on weight loss maintenance in adults after a clinically significant weight loss. As part of the trial, all participants received a FB tracker.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in accordance with the Helsinki Declaration and ethical approval has been granted by local institutional ethics committees at the Universities of Leeds (17-0082; 27-Feb-2017), Lisbon (17/2016; 20-Feb-2017) and the Capital Region of Denmark (H-16030495; 8-Mar-2017) and all participants provided informed consent to have their data used for research purposes by this research team. Full details of the trial protocol have been published previously [33]. The NoHoW trial recruited 1,627 participants and some of the observational work reported in this study utilised the entire sample of NoHoW participants and when this is the case, this is specified in the manuscript.…”
Section: Participantsmentioning
confidence: 99%